People importance and SHRD practices at ABC Multinational Organization Operating in Malaysia [electronic resource] - Farahnurhidayah Mohamed Fadil, 1986- (2016)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2016